Parokialitas Adat terhadap Pola Keberagamaan Komunitas Islam Wetu Telu di Desa Bayan Lombok - Zuhdi, Muhammad Harfin (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2006)
This article describes community-plurality pattern of Islam "Wetu Telu" of Bayan Wllagers, Lombok Barat, Nusa Tenggara Barat. They are strict adherent to their traditional beliefs in their rituals, so Â they become the target of dahuah (propagation) by Community "waktu lima" which consider themselves to have carried Islamic teaching in the right path. This research is qualitative in nature and employs cultural anthropology in its approach. The finding tells the readers that Wetu Telu are still Moslems who believe in Allah and His messenger, Muhammad. But in their ritual, they still have blended their Islamic teachings with their traditional beliefs. It is a living spirit they have maintained for a long time which worth respecting for a peace-co existence among them, the Moslem believers.